Exploring the role of gut microbiota in Parkinson’s disease: insights from fecal microbiota transplantation - Guo, Mengqi; Gao, Han; Wang, Yuan; Xiang, Yuanyuan (Frontiers in Neuroscience, 2025)
As a common neurodegenerative disease, Parkinson’s disease (PD) is typified by α-synuclein (α-syn) aggregation and progressive degeneration of dopaminergic neurons within the substantia nigra. Clinical manifestations encompass motor symptoms and non-motor aspects that severely impair quality of life. Existing treatments mainly address symptoms, with no effective disease-modifying therapies available. The gut microbiota refers to the community of microorganisms that colonize the intestinal tract. The gut microbiota, gut, and brain are all connected via a complicated, mutual communication pathway known as the “gut microbiota-gut-brain axis.” Gut microbiota dysbiosis is strongly linked to the onset and course of PD, according to growing data. In individuals with PD, gut dysbiosis correlates with clinical phenotype, disease duration, severity, and progression rates. Mechanistically, gut dysbiosis contributes to PD through enhanced intestinal permeability, increased intestinal inflammation and neuroinflammation, abnormal α-syn aggregation, oxidative stress, and reduced neurotransmitter synthesis. Therefore, focusing on the gut microbiota is regarded as a potentially effective treatment strategy. Fecal microbiota transplantation (FMT) is an emerging approach to modulate gut microbiota, with the goal of recovering microbiota diversity and function by transferring functional intestinal flora from healthy individuals into patients’ gastrointestinal tracts. FMT is expected to become a promising therapy of PD and has a broad research and application prospect. Evidence suggests that FMT may restore gut microbiota, ease clinical symptoms, and provide potential neuroprotective benefits. However, the precise therapeutic mechanisms of FMT in PD remain uncertain, necessitating further research to clarify its effectiveness. This review examines alterations in gut microbiota linked to PD, mechanisms through which gut dysbiosis influences the disease, and the latest advancements in FMT research for treating PD, setting the stage for its clinical application.